Super Geo-Bros Game: A Scratch-Based Mathematics Game for Learning Geometric Transformations to Improve Learning Outcomes - Fitrianingsih, Ajeng Nur Aulia; Rosjanuardi, Rizky; Sudihartinih, Eyus (FKIP Universitas Lampung, 2024)
This study aims to develop and evaluate the Super Geo-Bros game, an educational tool designed to assist ninth-grade students in understanding geometric transformations through interactive, Scratch-based technology. Following the ADDIE model, the research was conducted in five stages: analysis, design, development, implementation, and evaluation. The game allows students to interact with geometric shapes and perform transformations such as translation, rotation, reflection, and dilatation. Validation tests involving media and content experts demonstrated that the game is valid, practical, and effective, with a significant increase in students’ learning outcomes. The gain score of 0.71 indicates a high level of improvement, showing that this game enhances engagement and facilitates better comprehension of abstract mathematical concepts. Keywords: educational game, geometric transformation, mathematics learning, scratch, learning media.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp792-802